Technological properties of grain and flour in bread wheat (Triticum aestivum L.) genotypes carrying two loci that determine the endosperm structure - A. V. Simonov; T. A. Pshenichnikova (Труды по прикладной ботанике, генетике и селекции)
Background. The end-use of the bread wheat grain depends on the endosperm properties determined by the alleles of the Pina and Pinb genes at the Ha locus on chromosome 5D. The mealy (soft) endosperm is generated by the biosynthesis of puroindolines – complete proteins encoded by these genes. When milled, such grain breaks down into small starch granules covered with proteins. Mutations that disrupt the synthesis or structure of puroindolines determine the hardness and vitreousness of the grain. Earlier, we discovered a new locus for grain softness, Ha-Sp, introgressed from the diploid species Aegilops speltoides Tausch, which also determines the formation of the soft endosperm structure. By combining two active loci in one genotype, we produced a supersoft grain line (SSL). The aim of the present work was to verify the interaction of the two loci Ha and Ha-Sp in other wheat genotypes and evaluate the technological properties of grain and flour in comparison with the existing SSL line.Materials and methods. The F3–F8 hybrids from crosses of the soft-grain spring cultivars ‘Golubka’ and ‘Lutescens 62’, carriers of the Ha locus, with the introgressive line 84/98w, carrier of the Ha-Sp locus, were used in the work. Grain from three field seasons was studied according to milling parameters and physical properties of flour and dough.Results. At the early stages of selection (F3:4), the families with milling parameters typical of bread wheat were identified, as well as supersoft-grain families with a small flour particle size (9–10 μm) and low endosperm vitreousness (29–49%). Targeted selection made it possible to obtain lines similar to the SSL line in terms of milling performance and flour strength.Conclusion. For the first time, a set of supersoft-grain lines with special properties of grain and flour was obtained on the genetic basis of three spring cultivars. They may be in demand for a wide range of end-uses, including both food and nonfood production purposes.